2016
DOI: 10.1016/j.crad.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Digital breast tomosynthesis (DBT): a review of the evidence for use as a screening tool

Abstract: Breast screening with full-field digital mammography (FFDM) fails to detect 15-30% of cancers. This figure is higher for women with dense breasts. A new tomographic technique in mammography has been developed--digital breast tomosynthesis (DBT)--which allows images to be viewed in sections through the breast and has the potential to improve cancer detection rates. Results from retrospective reading studies comparing DBT with FFDM have been largely favourable with improvement in sensitivity and specificity. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 66 publications
4
88
0
5
Order By: Relevance
“…All these studies found significant improvement in cancer detection rate and a reduction in the overall recall rate or a reduction in the recall rate per cancer detected. Other investigators have conducted retrospective reader studies as reviewed in (11, 12); most of these studies also revealed the potential of the combo mode, yielding higher cancer detection rate and lower recall rate compared to DM alone.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies found significant improvement in cancer detection rate and a reduction in the overall recall rate or a reduction in the recall rate per cancer detected. Other investigators have conducted retrospective reader studies as reviewed in (11, 12); most of these studies also revealed the potential of the combo mode, yielding higher cancer detection rate and lower recall rate compared to DM alone.…”
Section: Introductionmentioning
confidence: 99%
“…First results on a reduction from 0.7 to 0.5 interval cancers per 100 screened women were very recently reported from a large study in the USA [31], but further evidence is needed. Moreover, the probable increase in reading time associated with the use of DBT in screening [32] and its effects on sustainability of screening programmes should be considered before routine implementation.…”
Section: The Potential Of Digital Breast Tomosynthesismentioning
confidence: 99%
“…DBT can reduce tissue overlap and improve the visualization of normal tissue and suspicious masses. A number of studies showed that DBT as an adjunct to mammography increased the sensitivity for detecting breast cancer and reduced recall rate in comparison to mammography alone (Ciatto et al 2013, Rose et al 2013, Skaane et al 2013a, Skaane et al 2013b, Friedewald et al 2014, Durand et al 2015, Bernardi et al 2016, Conant et al 2016, Gilbert et al 2016, Sharpe et al 2016). …”
Section: Introductionmentioning
confidence: 99%